1994
DOI: 10.1037/0096-1523.20.1.131
|View full text |Cite
|
Sign up to set email alerts
|

Visual-auditory interactions in sensorimotor processing: Saccades versus manual responses.

Abstract: Reaction times (RTs) to bimodal (visual and auditory) stimuli were examined using 3 different response systems: saccades, directed manual responses, and simple manual responses. The observed levels of intersensory facilitation exceeded race model predictions and therefore support summation (coactivation) models of bimodal processing. However, response-dependent differences suggest that the processing of bimodal targets also depends on the relevant sensorimotor pathways and requirements of the task. Coactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
188
6

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(213 citation statements)
references
References 35 publications
19
188
6
Order By: Relevance
“…Note that to clearly illustrate this relationship, only 1 significant interaction per neuron is contained within this plot because spontaneous activity was invariant across conditions. Again, the relationship was most apparent in the log-log transformed plot and points were best fit to the power function y ϭ 38.152 x Ϫ0.3615 with an r 2 ϭ 0.3401. multisensory responses may speed the time to the initiation of premotor activity in the SC (Bell et al 2001), a result that fits nicely with observations of multisensory-mediated speeding of eye movements (Corneil and Munoz 1996;Frens and Van Opstal 1998;Frens et al 1995;Harrington and Peck 1998;Hughes et al 1994), the role of the different subpopulations of SC multisensory neurons to this effect remain to be determined. From a mechanistic perspective, the current study illustrates that fundamental features of a given neuron's response characteristics are strong determinants of multisensory integration.…”
Section: Introductionsupporting
confidence: 52%
“…Note that to clearly illustrate this relationship, only 1 significant interaction per neuron is contained within this plot because spontaneous activity was invariant across conditions. Again, the relationship was most apparent in the log-log transformed plot and points were best fit to the power function y ϭ 38.152 x Ϫ0.3615 with an r 2 ϭ 0.3401. multisensory responses may speed the time to the initiation of premotor activity in the SC (Bell et al 2001), a result that fits nicely with observations of multisensory-mediated speeding of eye movements (Corneil and Munoz 1996;Frens and Van Opstal 1998;Frens et al 1995;Harrington and Peck 1998;Hughes et al 1994), the role of the different subpopulations of SC multisensory neurons to this effect remain to be determined. From a mechanistic perspective, the current study illustrates that fundamental features of a given neuron's response characteristics are strong determinants of multisensory integration.…”
Section: Introductionsupporting
confidence: 52%
“…It may, therefore, be concluded that the stage of processing at which the integration of the spatially congruent information occurs is not influenced by the response relevance of the stimulus components. A spatial congruency effect for bimodal stimuli has also been observed by Hughes et al (1994) when participants had to selectively elicit a saccade to a visual stimulus that was accompanied by an auditory distractor. By contrast, for manual responses, Hughes et al did not find a spatial congruency effect (however, only 3 Note-ANOVA results for the analysis outlined in Table 3A.…”
Section: Discussionmentioning
confidence: 94%
“…For bimodal divided attention tasks, the RT gain observed with bimodal stimuli is usually larger than that predicted by separate activation models, so that coactivation models have been adopted (Giray & Ulrich, 1993;Gondan, Lange, Rösler, & Röder, 2004;Hughes, ReuterLorenz, Nozawa, & Fendrich, 1994;Miller, 1982Miller, , 1986Miller, , 1991Molholm et al, 2002;Plat, Praamstra, & Horstink, 2000;Schröger & Widmann, 1998). Different loci at which the coactivation may take place have been suggested: Multisensory interactions may take place (1) at perceptual stages (Hershenson, 1962;Hughes et al, 1994;Molholm et al, 2002), (2) at higher cognitive stages (e.g., decision or memory; Miller, 1982;Mordkoff & Yantis, 1991;Schröger & Widmann, 1998), and/or (3) during motor preparation and execution (Diederich & Colonius, 1987;Giray & Ulrich, 1993; but see Miller, Ulrich, & Lamarre, 2001;Mordkoff, Miller, & Roch, 1996).…”
mentioning
confidence: 99%
“…In this case, their synergistic effects would enhance the likelihood of orienting to the initiating event, and this has been shown to be the case in behaving animals (Stein et al, 1988(Stein et al, , 1989Wilkinson et al, 1996;Stein, 1998;Jiang et al, 2002Jiang et al, , 2007Van Opstal and Munoz, 2004). Analogous multisensory benefits have also been repeatedly demonstrated in human subjects (Engelken and Stevens, 1989;Perrott et al, 1990;Hughes et al, 1994;Frens et al, 1995;Corneil and Munoz, 1996 The individual modalityspecific responses during the cortical deactivation and in the control condition were plotted together across all levels of stimulus effectiveness. A, During the cross-modal tests, the majority of the modality-specific responses in visual 1, visual 2, and auditory fell below the line of unity during the cortical deactivation.…”
Section: Cortico-sc Influence On Integration Is Multisensory-specificmentioning
confidence: 99%